2023
DOI: 10.1073/pnas.2218443120
|View full text |Cite
|
Sign up to set email alerts
|

Learning rules of engagement for social exchange within and between groups

Abstract: Globalizing economies and long-distance trade rely on individuals from different cultural groups to negotiate agreement on what to give and take. In such settings, individuals often lack insight into what interaction partners deem fair and appropriate, potentially seeding misunderstandings, frustration, and conflict. Here, we examine how individuals decipher distinct rules of engagement and adapt their behavior to reach agreements with partners from other cultural groups. Modeling individuals as Bayesian learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…First, there is some evidence that people can detect systematicity after ∼5 sequential actions and predict the next action above-chance level (Erev & Roth, 1998). Second, and relatedly, we have recently shown that people learn their opponent's acceptance levels in ultimatum bargaining games after approximately five interactions (Rojek-Giffin et al, 2023). Third, with discrete option space, five consecutive trials is the lowest number to identify deviations from four "systematic" strategies: stationary…”
Section: Studymentioning
confidence: 94%
See 1 more Smart Citation
“…First, there is some evidence that people can detect systematicity after ∼5 sequential actions and predict the next action above-chance level (Erev & Roth, 1998). Second, and relatedly, we have recently shown that people learn their opponent's acceptance levels in ultimatum bargaining games after approximately five interactions (Rojek-Giffin et al, 2023). Third, with discrete option space, five consecutive trials is the lowest number to identify deviations from four "systematic" strategies: stationary…”
Section: Studymentioning
confidence: 94%
“…First, there is some evidence that people can detect systematicity after ∼5 sequential actions and predict the next action above-chance level (Erev & Roth, 1998). Second, and relatedly, we have recently shown that people learn their opponent’s acceptance levels in ultimatum bargaining games after approximately five interactions (Rojek-Giffin et al, 2023). Third, with discrete option space, five consecutive trials is the lowest number to identify deviations from four “systematic” strategies: stationary ( t 0 = t 1 = t 2 = … = t 5 ); ascending ( t 0 ≤ t 1 ∧ t 0 < t 2 = … ≤ t 5 ∧ t 3 < t 5 ); descending ( t 0 ≥ t 1 ∧ t 0 > t 2 = … ≥ t 5 ∧ t 3 > t 5 ); and alternating ( t 0 > t 1 ∧ t 1 < t 2 ∧ t 2 > t 3 … or t 0 < t 1 ∧ t 1 > t 2 ∧ t 2 < t 3 …).…”
Section: Studymentioning
confidence: 98%
“…The more bonds they form, the more they learn about appropriate behavior, navigating interpersonal conflicts, and maintaining relationships. Repeated interactions with people from different groups allows individuals to learn how proper and improper social behavior vary across time and contexts (Rojek-Giffin et al, 2023). Individuals usually identify others in their environment who possess desirable resources, and then observe and imitate their behaviors (Heyes, 2016).…”
Section: The Value Of Social Valuementioning
confidence: 99%
“…Across repeated interactions and generations, cooperation becomes a beneficial strategy and over time instills socially shared norms that may be applied also with new partners one has no knowledge about. Such generalized expectations can already emerge after a few interactions ( Rojek-Giffin et al, 2023 ) but can also be part of a complex socialization process that is transmitted and shaped over generations ( Farina et al, 2021 ; Hare, 2017 ; Rand & Nowak, 2013 ). Either way, through generalized norms, individuals develop social preferences for cooperation that, to some degree, become independent of others’ reputation or group membership (see also Box 1 ) and how one’s own and others’ payoffs are correlated.…”
Section: The Formation and Evolution Of Groupsmentioning
confidence: 99%